Diagnostic Test Accuracy of Serum Anti-PLA2R Autoantibodies and Glomerular PLA2R Antigen for Diagnosing Idiopathic Membranous Nephropathy: An Updated Meta-Analysis - Li, Weiying; Zhao, Yuliang; Fu, Ping (Frontiers in Medicine, 2018)
Background: M-type phospholipase A2 Receptor is known as a major antigen on podocytes which is involved with the pathogenesis of idiopathic membranous nephropathy (iMN). Many studies have shown that serum anti-PLA2R autoantibodies (sPLA2R) is prevalent in patients with iMN but are rarely detected in secondary membranous nephropathy (SMN) or other glomerulonephritis. The anti-PLA2R is considered as a promising serum biomarker in iMN but reports about its diagnostic value are variable and inconsistent. Objective: To evaluate the diagnostic test accuracy of anti-PLA2R and glomerular PLA2R antigen (gPLA2R) for diagnosing iMN. Method: MEDLINE, EMBASE, WEB OF SCIENCE and COCHRANE LIBRARY were searched from 2009 Jan to Feb 2018. Heterogeneity was evaluated by Q test and I2. Source of heterogeneity was explored by subgroup analysis and meta-regression. Meta-analysis was executed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. Results: Totally thirty-five studies were retrieved under the pre-set study eligibility criteria. Twenty-eight studies were included to evaluate the diagnostic test accuracy of anti-PLA2R for differentiating iMN from non-iMN. They indicated a pooled sensitivity of 65% (63% to 67%), specificity of 97% (97% to 98%), positive likelihood ratio of 15.65 (9.95 to 24.62) and negative likelihood ratio of 0.37 (0.32 to 0.42) with a Diagnostic OR (sDOR) of 50.41 (31.56 to 80.52) and AUC of 0.9393. No threshold effect was detected. The heterogeneity analysis for sDOR showed that I2 =50.3% and Conchran-Q=54.29, df=27 (p=0.0014). Heterogeneity was significant. Meta-regression revealed that sample size might be the potential source of heterogeneity. Subgroup analysis demonstrated that method type and ratio of patients with nephrotic-range proteinuria at baseline might be the source of heterogeneity. Sixteen studies reported the diagnostic value of glomerular PLA2R antigen for differentiating iMN from non-iMN. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, sDOR and AUC were 79% (76 to 81%), 90% (88% to 92%), 8.17 (5.60 to 11.93), 0.25 (0.19 to 0.33), 39.37 (22.18 to 60.13) and 0.9278. Heterogeneity analysis showed that Cochran-Q=35.36; df=15 (p=0.002), and I2 for sDOR was 57.6%. Conclusion: sPLA2R and gPLA2R demonstrated a good diagnostic accuracy in differentiating iMN and non-iMN.